A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia - Khan, Mohd Talib; Ahmad, Syed Kamran; Anis, Shoeba Binte; Dawah, Hassan Ali (Zootaxa, 2018)
The genus Xiphogramma Nowicki (1940) is recorded for the first time from the Kingdom of Saudi Arabia, with the description of a new species, Xiphogramma hayati sp. nov. An updated key to the world species of this genus is also provided.